Keluarga Sakinah Berwawasan Gender - Muslim Arma (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2017)
Every adherent of a religion, believes in the truth of every doctrine that is in his religion, whether in worship or in daily life, such as life in marriage. According to Muslim femenis that the interpretation of the Qur'an and the Hadith of the Prophet related to women often discriminate against women, resulting in the abuse of violence against women. The conclusion is, the content of truth contained in religion (especially Islam), if carried out in accordance with the guidance of the Qur'an and Sunnah, it will gradually give a positive influence on every Muslim individual, including in realizing a sakinah family of gender perspective.